Systematic review of the health and social determinants and outcomes of home cooking: protocol - Mills, Susanna (Syst Rev, 2015)
BACKGROUND: The United Kingdom (UK) and wider world are experiencing an obesity epidemic, with lower socio-economic groups disproportionately affected. Dietary quality is also socio-economically patterned, with an estimated quarter of observed inequalities in UK mortality due to inequalities in diet. Food preparation and eating patterns clearly have an impact on dietary intake and hence health. A growing body of evidence indicates that out of home food consumption and eating ready meals may be associated with negative outcomes. However, to date no systematic reviews have assessed the health and social determinants and outcomes of home cooking. Here, home cooking refers to the combination of actions required for preparing hot or cold foods at home, including combining, mixing and often heating ingredients. METHODS/DESIGN: A systematic review of peer-reviewed literature on home cooking will be undertaken. Studies will be considered for inclusion if they present qualitative or quantitative data on participants from high/very high human development index countries, including all relevant study designs. No language or date of publication restrictions will be applied. Determinants will be considered as factors that influence behaviour and outcomes as potential advantages and disadvantages of engaging in home cooking. Electronic databases of peer-reviewed journal articles covering health, psychology, social sciences and consumer practices will be searched. Published postgraduate theses will also be considered for inclusion. Additional strategies to identify relevant studies will be used, such as citation searches of included articles, evaluation of references from relevant reviews and included articles and the ‘related/similar to’ function found in certain databases. Two independent researchers will be involved in literature screening (10% at first screen and 100% at second screen), data extraction and quality appraisal. Studies included in the review will be analysed by thematic synthesis and narrative synthesis, as appropriate for the nature of the data retrieved. DISCUSSION: This review will provide key empirical evidence to inform the development of recommendations for public health policy makers and practitioners to encourage healthier home food preparation, thereby impacting on dietary-related health. SYSTEMATIC REVIEW REGISTRATION: This protocol has been registered with the PROSPERO international prospective register of systematic reviews, reference CRD42014013984. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13643-015-0033-3) contains supplementary material, which is available to authorized users.